Teacher’s Perception toward the Use of English for Communication Science Book - Weny Anita Febriantini; Johannes Ananto Prayogo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: This study aimed at investigating the teachers’ perception toward the use of English for Communication Science book and how it facilitates the teaching learning process. Descriptive qualitative research was applied in this study. According to the data obtained from questionnaire and interview, the textbook has fulfilled several criteria of a good book: practicality, language use and content, topics, and tasks. However, it has not fulfilled other criteria: suitability to students, skills mastery, relation to syllabus, and design and organization. In addition, the criteria which facilitate the teaching learning process are language use and content and topics.Abstrak: Penelitian ini bertujuan untuk mengetahui persepsi guru terhadap penggunaan buku English for Communication Science dan bagaimana buku tersebut memudahkan dalam proses belajar mengajar. Metode yang digunakan adalah deskriptif kualitatif. Menurut data yang diperoleh dari kuesioner dan interview, buku tersebut telah memenuhi kriteria buku yang baik dalam hal kepraktisan, bahasa dan isi, topic, dan soal latihan, sedangkan belum terpenuhi dalam hal kesesuaian terhadap mahasiswa, penguasaan ketrampilan, kesesuaian dengan silabus, dan desain organisasi. Dengan demikian, kriteria yang dapat memudahkan dalam proses belajar mengajar adalah bahasa dan isi dan topik yang berhubungan dengan jurusan ilmu komunikasi.